Active material, electrode, secondary battery, battery pack, and vehicle

By using Li a Ti b Nb 2 W c O 2b+3c+5+δ composite oxide as the active material of lithium-ion secondary batteries, the problems of dendrites deposition and low energy density during fast charging and discharge of lithium-ion secondary batteries are solved, and battery performance with high capacity and high energy density is achieved.

JP2025044404APending Publication Date: 2025-04-02KK TOSHIBA
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023151957
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-02

AI Technical Summary

Technical Problem

Existing lithium-ion secondary batteries are prone to deposition of lithium metal dendrites during fast charging and discharging, resulting in internal short circuits, heat generation and combustion. The theoretical capacity of carbon-based negative electrode materials is low, limiting the energy density of the battery.

Method used

Li a Ti b Nb 2 W c O 2b+3c+5+δ composite oxide is used as the active material, which has a monoclinic crystal and a square crystal structure. By adjusting the proportions of Li, Ti, Nb, W and the heating temperature, the crystal structure and phase combination are adjusted, thereby improving the capacity and cycling stability of the battery.

Benefits of technology

A lithium-ion secondary battery with high capacity and high energy density is realized, which improves the cycling stability and safety performance of the battery and avoids the problems of dendritic deposition and internal short circuit.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025044404000001_ABST
    Figure 2025044404000001_ABST
Patent Text Reader

Abstract

To provide an active material and an electrode capable of realizing a high-capacity secondary battery, a high-capacity secondary battery and a battery pack, and a vehicle equipped with the battery pack.SOLUTION: An active material according to an embodiment includes a complex oxide represented by the general formula of LiaTibNb2WcO2b+3c+5δ, 0≤a≤b+3c+4, <b<2, 0<c<2, and 1.9b+2.85c+4.75≤δ≤2.1b+3.15c+5.25. The complex oxide has at least one of a monoclinic structure and an orthorhombic structure.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE Embodiments of the present invention relate to an active material, an electrode, a secondary battery, a battery pack, and a vehicle. [Background technology]

[0002] In recent years, research and development of secondary batteries such as lithium ion secondary batteries and nonaqueous electrolyte secondary batteries as high energy density batteries has been actively promoted. Secondary batteries are expected to be used as power sources for vehicles such as hybrid cars and electric cars, or as uninterruptible power sources for mobile phone base stations. Therefore, in addition to energy density, secondary batteries are also required to have other excellent performances such as rapid charge and discharge performance and long-term reliability.

[0003] A typical negative electrode for a lithium-ion secondary battery is a carbon-based negative electrode that uses a carbonaceous material such as graphite as the active material. When a battery using a carbon-based negative electrode is repeatedly charged and discharged rapidly, dendrites of metallic lithium are deposited on the electrode, which may cause an internal short circuit and cause heat generation or fire. Therefore, a battery has been developed that uses a metal composite oxide instead of a carbonaceous material for the negative electrode, thereby increasing the negative electrode operating potential. For example, the spinel-type lithium titanium composite oxide Li4Ti5O 12 The battery using this as the negative electrode has an average operating potential of 1.55 V (vs. Li / Li + ), the precipitation of Li dendrites does not progress, making stable rapid charging and discharging possible, and since it operates at a potential where reduction side reactions of the electrolyte are unlikely to occur, it has a longer life than batteries using carbon-based anodes. 12 The theoretical capacity of the active material used in the negative electrode was low at 175 mAh / g, and compared to batteries with carbon-based negative electrodes, it had the problem of low energy density.

[0004] Therefore, the tetragonal niobium-titanium composite oxide Ti2Nb 10 W5O 44 and TiNb2WO 10is being considered. Based on the oxidation-reduction potential of lithium, 1V (vs. Li / Li + ) while exhibiting high capacity. For this reason, it is expected that the volumetric energy density will exceed that of carbon-based anodes. However, in order to fully popularize electric vehicles, it is desirable to further increase the energy density of lithium-ion secondary batteries from the viewpoint of improving driving range, and it is therefore desirable to develop a high-capacity quick-charge battery. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2012-99287 A [Patent Document 2] JP 2022-145421 A [Non-patent literature]

[0006] [Non-Patent Document 1] Nature, 559, 556-563 (2018) Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an active material and an electrode capable of realizing a high-capacity secondary battery, a high-capacity secondary battery and a battery pack, and a vehicle equipped with the battery pack. [Means for solving the problem]

[0008] According to an embodiment, the general formula Li a Ti b Nb2W c O 2b+3c+5+δProvided is an active material containing a composite oxide represented by 0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25, and having a crystal structure of at least one of a monoclinic structure and an orthorhombic structure.

Brief Description of Drawings

[0009] [Figure 1] Schematic diagram showing the crystal structure of an example of the composite oxide contained in the active material according to the embodiment. [Diagram 2] Schematic diagram showing the crystal structure of another example of the composite oxide contained in the active material according to the embodiment. [Diagram 3] Cross-sectional view schematically showing an example of a secondary battery according to the embodiment. [Figure 4] Enlarged cross-sectional view of part A of the secondary battery shown in FIG. 3. [Diagram 5] Partial cutaway perspective view schematically showing another example of a secondary battery according to the embodiment. [Figure 6] Enlarged cross-sectional view of part B of the secondary battery shown in FIG. 5. [Figure 7] Perspective view schematically showing an example of a battery pack according to the embodiment. [Figure 8] Exploded perspective view schematically showing an example of a battery pack according to the embodiment. [Figure 9] Block diagram showing an example of the electrical circuit of the battery pack shown in FIG. 8. [Figure 10] Partial transparent view schematically showing an example of a vehicle according to the embodiment. [Figure 11] Diagram schematically showing an example of a control system related to the electrical system in a vehicle according to the embodiment. [Figure 12] Diagram showing an atomic image observed using a scanning transmission electron microscope of the active material composite oxide in Example 1. [Figure 13] Diagram showing an atomic image observed using a scanning transmission electron microscope of the active material composite oxide in Comparative Example 1. [Figure 14] Graph showing the first charge-discharge curves in Example 1 and Comparative Example 1.

Best Mode for Carrying Out the Invention

[0010] Hereinafter, embodiments will be described with reference to the drawings. In the following description, components that exhibit the same or similar functions are given the same reference numerals throughout all the drawings, and duplicate explanations are omitted. Also, each drawing is a schematic diagram for facilitating the explanation of the embodiments and their understanding. Although the shape, dimensions, ratio, etc. are different from those of the actual device, these can be appropriately changed in design in consideration of the following explanation and known techniques.

[0011] [First Embodiment] According to the first embodiment, an active material containing a composite oxide having at least one crystal structure of a monoclinic structure and an orthorhombic structure is provided. The composite oxide has the general formula Li a Ti b Nb2W c O 2b+3c+5+δ and is represented by. Each subscript in the formula satisfies 0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, and 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25, respectively. The active material according to the embodiment can contain trace additive elements as described later, and a form in which the trace additive elements are included in the composite oxide as substitution elements is also included in the first embodiment. However, in the above general formula, a composition in which the trace additive elements are omitted is represented.

[0012] The active material according to the embodiment can be an active material for a battery. The active material can be, for example, an electrode active material used for an electrode of a secondary battery such as a lithium-ion battery or a non-aqueous electrolyte. More specifically, the active material can be, for example, a negative electrode active material used for the negative electrode of a secondary battery.

[0013] The above general formula Li a Ti b Nb2W c O 2b+3c+5+δIt is represented by (0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25). By using a composite oxide having at least one crystal structure of a monoclinic structure and an orthorhombic structure as an electrode active material, a high-capacity secondary battery can be realized.

[0014] The composite oxide contained in the active material according to the embodiment corresponds to a part of an oxide material having a Wadsley-Roth phase structure, which is a crystal phase in an oxide material containing niobium. The Wadsley-Roth phase has, for the ratio of oxygen O to metal element M in the composition, the number of oxygen atoms and the number of metal element atoms as A O and A M respectively, and it has been reported that it takes a crystal structure in the range of 2.33≦A O / A M ≦2.65. For example, in the case of TiNb2O7, it has a crystal structure on the reducing side where A O / A M = 2.33.

[0015] Here, reduction means that the proportion of oxygen in the structure is low. The Wadsley-Roth phase has a structure in which the vertex-sharing structure of oxygen-metal octahedrons forms a block structure of the rhenium oxide type, and the blocks share the edges of the octahedrons, or tetrahedrons intervene and share the vertices, so that the rhenium oxide type blocks (ReO3 type blocks) are connected in the two-dimensional direction. The size of the block is such that the number of octahedrons is 4×4 = 16. The crystal structure on the reducing side has a structure with a small size of the rhenium oxide type block. The rhenium oxide type crystal structure has voids into which a large amount of lithium (Li) can be inserted, but it is a highly symmetric crystal structure. In order to eliminate the charge repulsion when Li is inserted, it is difficult to change the bond length between the metal element and the oxygen element. Therefore, it can be said that the rhenium oxide type crystal structure has a structure in which the insertion of Li is restricted due to the charge repulsion when Li is inserted. Here, making it the crystal structure on the reducing side means A O / A MSince it becomes small, the number of oxygen atoms in the structure decreases, so the size of the ruthenium oxide type block becomes small. As a result, when Li is inserted, a crystal structure capable of volume expansion due to the change in the bond length between the metal element and the oxygen element can be obtained. Therefore, by including the ruthenium oxide type crystal structure, although it has wide voids, there are no restrictions on the structural change when Li is inserted, so a large amount of Li can be inserted.

[0016] Regarding the composite oxide contained in the active material according to the embodiment, by adopting a crystal structure on the reduction side like TiNb2O7, it becomes possible to insert more lithium (Li) into the crystal structure, and a crystal structure with a large reversible capacity is obtained. That is, the crystal structure of the composite oxide contained in the active material according to the embodiment is a crystal structure on the reduction side belonging to the Wadsley-Roth phase composed of three elements including titanium, a tetravalent element with a low valence number.

[0017] General formula Li a Ti b Nb2W c O 2b+3c+5+δ In this case, the subscripts a, b, c, and δ can be respectively included within the ranges of 0 ≦ a ≦ b + 3c + 4, 0 < b < 2, 0 < c < 2, and 1.9b + 2.85c + 4.75 ≦ δ ≦ 2.1b + 3.15c + 5.25. It is preferable that the subscripts b and c are respectively within the ranges of 0.4 ≦ b ≦ 1.6 and 0.4 ≦ c ≦ 1.6, and more preferably within the ranges of 0.6 ≦ b ≦ 1.2 and 0.6 ≦ c ≦ 1.2.

[0018] General formula Li a Ti b Nb2W c O 2b+3c+5+δ As an example of the monoclinic titanium-niobium-tungsten composite oxide represented by, a schematic diagram of the crystal structure of Ti4Nb 10 W4O 45 is shown in FIG. 1. In FIG. 1, the unit cell in the

[0010] direction when the crystal structure is viewed along the b-axis direction is shown. Note that the stoichiometric ratio in the composite oxide is represented as Ti4Nb 10 W4O 45 However, although the composition is represented as such, the composition is Ti 0.8Nb2W 0.8 The crystal structure has a space group notation of P21 / n and a space group number of 14. The space group in this case corresponds to the contents of Vol. A: Space-group symmetry in the "International Tables for Crystallography" (2nd online edition (2016); ISBN: 978-0-470-97423-0, doi: 10.1107 / 97809553602060000114).

[0019] Here, the space group is not limited to P21 / n, and other space groups belonging to space group number 14, such as P21 / c, P21 / a, and P21 / b, can also be explained by coordinate transformation, and are equivalent crystal structures. In addition, although the crystal structure in FIG. 2 has the b axis as the unique axis, it can also be set to the a axis and b axis, and is not limited thereto. Ti4Nb 10 W4O 45 So, the number of atoms of metal element M (including Ti, Nb, and W) is A M A is the number of oxygen atoms O The ratio of A O / A M = 2.50. Octahedrons 10a each composed of a metal element 18 and an oxygen element 19 are included in the monoclinic crystal structure 10. The octahedrons 10a are connected to each other by corner sharing to form a rhenium oxide type block (ReO3 type block). The size of the block is 4 x 4 = 16 octahedra. The rhenium oxide type block forms planes in the a-axis direction and the c-axis direction by sharing the edges of the octahedrons 10a. A crystal structure is formed by connecting multiple planes including these 16 octahedra 10a on the c-axis side by octahedral corner sharing.

[0020] General formula Li a Ti b Nb2W c O 2b+3c+5+δ As an example of an orthorhombic titanium-niobium-tungsten composite oxide represented by the formula Ti4Nb 10 W4O 45A schematic diagram of the crystal structure of Ti4Nb is shown in FIG. 2. In FIG. 2, the crystal structure is shown as a unit cell in the

[0010] direction as viewed along the b-axis direction. The stoichiometric ratio of the complex oxide is Ti4Nb 10 W4O 45 However, the composition is Ti 0.8 Nb2W 0.8 The crystal structure is assigned the space group Amma and the space group number is 63. The space group corresponds to the contents of Vol. A: Space-group symmetry in the International Tables for Crystallography (2nd online edition (2016); ISBN: 978-0-470-97423-0, doi: 10.1107 / 97809553602060000114).

[0021] Here, the space group is not limited to Amma, and other space groups belonging to space group number 63, such as Cmcm, Ccmm, Amam, Bbmm, and Bmmb, can also be explained by coordinate transformation, and are equivalent crystal structures. Ti4Nb 10 W4O 45 So, the number of atoms of metal element M (including Ti, Nb, and W) is A M A is the number of oxygen atoms O The ratio of A O / A M = 2.50. The orthorhombic crystal structure 11 contains octahedrons 10a each composed of a metal element 18 and an oxygen element 19. The octahedrons 10a are connected to each other by corner sharing to form a rhenium oxide type block (ReO3 type block). The size of the block is 4 x 4 = 16 octahedra. The rhenium oxide type block forms planes in the a-axis direction and the c-axis direction by sharing the edges of the octahedrons 10a. A crystal structure is formed by connecting multiple planes including these 16 octahedra 10a on the c-axis side by octahedral edge sharing.

[0022] Generally, tungsten-niobium composite oxides have a crystal structure with a high tungsten composition ratio, and the crystal structure includes a block structure with a block size of 4 × 5 = 20 or 5 × 5 = 25. The titanium-niobium-tungsten composite oxide, which is an aspect of the first embodiment, has been achieved as a result of the inventors' discovery that by including titanium, a tetravalent element with a low valence number, the block structure can be reduced even in a state with a high tungsten composition ratio. By reducing the block size, it becomes possible to improve the insertion amount of lithium (Li). Also, since tungsten belongs to the sixth-period elements, it is a heavier element compared to titanium and niobium elements, and thus a material with an improved true density can be obtained compared to conventional TiNb2O7. As a result, it becomes possible to improve the capacity per unit mass.

[0023] Regarding the active material according to the embodiment, the crystal structure of the composite oxide can take, for example, the crystal structure illustrated in FIG. 1, the crystal structure illustrated in FIG. 2, or a crystal structure in which both are mixed. The above general formula Li a Ti b Nb2W c O 2b+3c+5+δ The range of the composition represented by can be taken in the range of 0 ≦ a ≦ b + 3c + 4, 0 < b < 2, 0 < c < 2, 1.9b + 2.85c + 4.75 ≦ δ ≦ 2.1b + 3.15c + 5.25 for each subscript in the formula. In any case within this range, a high-capacity active material material can be obtained, and the composition can be selected according to the battery design.

[0024] Generally, tungsten element (W) and titanium element (Ti) are elements that are likely to enter the structure in the Wadsley-Roth phase, in which there are many polytypes with different composition ratios. Therefore, the replacement of niobium element (Nb) in the structure is easier compared to other elements. Therefore, by combining these elements of W, Ti, and Nb, it is possible to adjust the composition ratio in the crystal structure.

[0025] In the active material according to the present invention, the mixture ratio of the monoclinic structure and the orthorhombic structure is such that the composition ratio of both structures and the metal / oxygen composition ratio are the same, so that a phase is obtained in a state in which two phases coexist. The composition ratio is not limited, but can be adjusted. This can be achieved by adjusting the sintering temperature to adjust the uneven distribution state of the metal element, or by adjusting the composition ratio to adjust the valence balance of the metal element in the crystal structure to adjust the uneven distribution state. It is considered that the mixture ratio of the monoclinic structure can be increased when the sintering temperature is higher than 1100°C, or when the ratio of Ti / W element in the active material is adjusted to be higher. It is considered that the mixture ratio of the orthorhombic structure can be increased when the sintering temperature is lower than 1100°C, or when the ratio of Ti / W element in the active material is adjusted to be lower. By increasing the mixture ratio of the orthorhombic structure, it is possible to increase the theoretical capacity of the battery.

[0026] In the active material according to the present invention, the monoclinic structure and the orthorhombic structure are arranged to form domains with each other in the primary particles. Between the domains of the monoclinic structure and the orthorhombic structure, 4×4=16 block structures are connected by edge sharing, and it is possible to form a strong bond without forming defects. Therefore, it is possible to have a structure that is strong against volume expansion and contraction during Li absorption and release, and suppresses cracking within the primary particles. It is more preferable to make either structure a single phase. If the crystal structure is different, the uneven distribution state of the metal element changes, which changes the Li insertion behavior, and the behavior of the volume expansion and contraction during Li absorption and release changes. This is because if the structure of the active material is different within the primary particles, there is a possibility that cracks due to hysteresis will occur if there are lattice defects present between the phases.

[0027] As for the specific ratio of the monoclinic structure and the orthorhombic structure, it is preferable to determine the mixture ratio by performing the Rietveld analysis described later on both crystal structures, but as a simpler method, it is possible to estimate by checking the peak position around 2θ = 30 ° to 40 °. As peaks characteristic of the monoclinic structure around 2θ = 30 ° to 40 °, there are a peak attributable to Miller index (41-3) appearing in the range of 2θ = 31.86 ± 0.10, a peak attributable to Miller index (31-4) appearing in the range of 2θ = 33.11 ± 0.10, a peak attributable to Miller index (90-1) appearing in the range of 2θ = 35.26 ± 0.10, and a peak attributable to Miller index (107) appearing in the range of 2θ = 36.51 ± 0.10, and there are no peaks with clear intensity in the orthorhombic structure at these peak positions. On the other hand, peaks characteristic of the orthorhombic structure include a peak attributable to Miller index (806) that appears in the range of 2θ = 31.63 ± 0.10, and a peak attributable to Miller index (808) that appears in the range of 2θ = 35.95 ± 0.10, but there are no peaks with clear intensities at these peak positions in the monoclinic structure. By checking the presence or absence of the above peaks and their intensity ratios, the mixed state can be estimated.

[0028] <Minor additive elements> In the active material according to the embodiment, the performance can be further improved by adding an element to the composite oxide. a Ti b Nb2W c O 2b+3c+5+δ In addition to the composite oxide having at least one of a monoclinic structure and an orthorhombic structure, which is represented by the formula (1), a trace amount of an additive element may be contained. The elements include V, Ta, Fe, Bi, Sb, As, P, Cr, Mo, B, Na, K, Mg, Al, Ca, Y, Zr, and Si.

[0029] The additive element may be included in the structure in a form substituting a part of the constituent elements of the composite oxide. a Ti bNb2W c O 2b+3c+5+δ The present invention also includes a substitution oxide based on a composite oxide having at least one of a monoclinic structure and an orthorhombic structure, represented by the following formula: In addition, the above-mentioned additive element may be present in the active material in a form that is not included in the crystal structure of the composite oxide.

[0030] For example, vanadium (V) and phosphorus (P) elements can be incorporated into the crystal structure as pentavalent elements. By partially replacing the tetravalent titanium (Ti) element contained as a basic constituent element with a pentavalent element, the electronic conductivity of the active material can be improved. This can improve the rate performance and life performance of the active material. Therefore, by performing element replacement with V and / or P, it is possible to adjust the curve shape of the battery.

[0031] Elements selected from vanadium (V), molybdenum (Mo), boron (B), sodium (Na), and potassium (K) have a low melting point of the composite oxide, and therefore can be effective as sintering aids. By adding trace amounts of these elements, it is possible to lower the sintering temperature during the synthesis of the composite oxide and improve the crystallinity. By increasing the crystallinity, it is possible to improve the rate performance and cycle performance of the active material.

[0032] Tantalum (Ta) is a pentavalent element that can replace Nb. Ta and Nb are in the same group on the periodic table, so they have similar physical and chemical properties. Therefore, it is possible to obtain the same battery performance even if Nb is replaced with Ta.

[0033] An element selected from iron (Fe), chromium (Cr), aluminum (Al), bismuth (Bi), antimony (Sb), and arsenic (As) can be incorporated into the crystal structure as a trivalent element. Magnesium (Mg) can be incorporated into the crystal structure as a divalent element. By replacing a portion of the Ti element with a trivalent or divalent element, it is possible to increase the composition ratio of the hexavalent W element in order to maintain electrical neutrality in the structure. This makes it possible to increase the theoretical capacity of the battery and further increase the amount of Li inserted into the active material.

[0034] Elements such as calcium (Ca), zirconium (Zr), yttrium (Y), and silicon (Si) are elements whose oxides can exist stably under the firing conditions in the synthesis of the composite oxide, and are elements that are not substituted in the crystal structure. The presence of trace amounts of these elements can function as grain growth inhibitors that suppress grain growth during firing. This allows the shape of the particle size distribution to be regulated, and makes it possible to further suppress uneven distribution of the particle size distribution.

[0035] It is desirable that one or more elements selected from the group consisting of V, Ta, Fe, Bi, Sb, As, P, Cr, Mo, B, Na, K, Mg, Al, Ca, Y, Zr, and Si are contained in a small amount. a Ti b Nb2W c O 2b+3c+5+δ In the active material according to the embodiment, the composition of the composite oxide is represented by the general formula Li a Ti b Nb2W c O 2b+3c+5+δHowever, the formula does not exclude substituted complex oxides containing a minor substitution element incorporated in the crystal structure. Naturally, the minor addition element not incorporated in the crystal structure of the complex oxide is not expressed in the general formula above, but the active material according to the embodiment also includes a form containing the above element in addition to the complex oxide. The active material according to the embodiment is an unsubstituted Li a Ti b Nb2W c O 2b+3c+5+δ It may be a composite oxide.

[0036] <Active material particles> The active material according to the first embodiment may be in the form of particles, for example. That is, the active material according to the embodiment may be represented by the general formula Li a Ti b Nb2W c O 2b+3c+5+δ The active material according to the embodiment may be composed of particles of a complex oxide having at least one of a monoclinic structure and an orthorhombic structure, represented by the formula (with or without a minor substitution element). The active material according to the embodiment may be composed of particles containing a mixture of the above-mentioned elements that can be added in trace amounts in addition to the complex oxide. The active material may be a single primary particle, a secondary particle formed by agglomeration of a plurality of primary particles, or a mixture of these. The active material may contain the above-mentioned elements, for example, on the surface of the primary particles of the complex oxide or between the primary particles of the complex oxide.

[0037] The average primary particle size of the active material according to the embodiment is preferably 10 μm or less, more preferably 5 μm or less, and even more preferably 3 μm or less. If the average primary particle size of the active material is small, the diffusion distance of lithium ions in the primary particles is short, so that lithium ion diffusibility tends to increase. In addition, if the average primary particle size of the active material is small, the reaction area increases, so that the reactivity between the active material and lithium ions increases, and the lithium ion insertion / extraction reaction tends to proceed.

[0038] The average secondary particle diameter of the active material according to the embodiment is preferably 1 μm or more and 50 μm or less. By setting the average secondary particle diameter of the active material within this range, it is possible to improve the productivity during electrode production and obtain a battery with good performance. This average secondary particle diameter means the particle diameter at which the volume cumulative value is 50% in the particle size distribution determined by a laser diffraction type particle size distribution measuring device.

[0039] The BET specific surface area of ​​the active material is 3.0m 2 / g or more 120m 2 / g or less is desirable, and 4.0m 2 / g or more 110m 2 / g or less is more preferable. By using an active material with a high specific surface area, the discharge rate performance of the battery can be improved. In addition, by using an active material with a low specific surface area, the life performance of the battery can be improved, and the coating property of the slurry containing the active material can be improved in the manufacturing process of the electrode described later in the second embodiment.

[0040] The BET specific surface area refers to the specific surface area determined by the nitrogen BET (Brunauer, Emmet and Teller) method. The method for determining the specific surface area based on the nitrogen BET method will be described in detail later.

[0041] <Manufacturing method> The active material according to the embodiment can be manufactured as follows. The manufacturing method of the titanium-niobium-tungsten composite oxide is not particularly limited, but it can be synthesized by, for example, a solid-phase reaction method, a sol-gel method, a hydrothermal synthesis method, etc. As an example, the solid-phase reaction method and the sol-gel method will be described.

[0042] (Solid-state reaction method) The solid-phase reaction method uses a titanium compound, a niobium compound, and a tungsten compound as starting materials. Examples of titanium compounds include titanium hydroxide, anatase-type titanium oxide, and rutile-type titanium oxide. Examples of niobium compounds include niobium hydroxide and niobium oxide. Examples of tungsten compounds include ammonium paratungstate and its hydrates, ammonium tungstate and its hydrates, tungsten hydroxide, and tungsten oxide.

[0043] When producing a substituted composite element in which a part of titanium, niobium, or tungsten in the crystal structure is replaced with a trace amount of the above-mentioned element (trace additive element), for example, an oxide of the element to be introduced as the substitution element can be included in the starting material.

[0044] As the starting material, for example, a particulate material is used. The average particle size of the starting material is 5 μm or less, more preferably 2 μm or less. In the solid-state reaction method, the reaction proceeds from the contact points between particles, so by reducing the particle size, it is possible to increase the reactivity, making it easier to obtain the target phase.

[0045] After weighing out the starting materials in a predetermined composition ratio, the materials are thoroughly mixed. Mixing can be done by either a wet method or a dry method. After mixing the materials, the mixture is fired.

[0046] Generally, the temperature at which the sublimation of oxides containing W element progresses significantly is 1400K (1127℃) or higher, and it is preferable to set the firing temperature below that, but it is difficult to obtain a uniform phase by firing this material at the aforementioned temperature. One method for obtaining a uniform phase at a low temperature and in a short time is to make the average particle size of the raw material compound containing W element smaller. In solid-phase sintering, the reaction proceeds with thermal diffusion starting from the solid joint as the driving force. Here, by making the particles of the raw material containing W element, which has a low melting point, smaller, the interparticle joint area during sintering can be increased because it passes through the liquid phase. Furthermore, the reaction surface increases as the contact points of the particles increase. As a result, the surface energy decreases, making it possible to proceed sintering well, and a uniform phase can be obtained while suppressing the sublimation of W element.

[0047] The firing process may include pre-firing before the main firing. Pre-firing is preferably performed at a firing temperature of 800°C or higher and 1100°C or lower for a firing time of 5 hours to 20 hours. A solid-phase reaction can proceed within this firing temperature and firing time range. Pre-firing before the main firing allows the reaction to occur in advance, which can increase reactivity.

[0048] The firing temperature for the main firing is preferably 900° C. or higher and 1100° C. or lower, more preferably 1000° C. or higher and 1100° C. or lower. The firing time is preferably 5 hours or higher and 20 hours or lower. Within this firing temperature and firing time range, it is possible to proceed with the solid-phase reaction and obtain the desired crystal phase.

[0049] After cooling, the raw material is pulverized by a pulverizer until it has a predetermined average particle size. When pulverizing, the crystallinity of the active material may be reduced due to mechanical impact. In this case, it is preferable to restore the crystallinity by annealing and firing again. The annealing and firing temperature is preferably 800°C or higher and 1000°C or lower, and the firing time is preferably 1 hour or higher and 5 hours or lower.

[0050] (Sol-gel process) In the sol-gel method, titanium compounds, niobium compounds, and tungsten compounds are used as starting materials. Examples of titanium compounds include titanium tetraisopropoxide, titanyl sulfate, titanium chloride, titanium ammonium oxalate and its hydrate, and titanium hydroxide. Examples of niobium compounds include niobium chloride, niobium ammonium oxalate and its hydrate, and niobium hydroxide. Examples of tungsten compounds include tungsten chloride, ammonium paratungstate and its hydrate, and tungsten hydroxide.

[0051] It is preferable to dissolve the starting materials in pure water or acid in advance to prepare a solution. By dissolving the starting materials, it is possible to obtain a dry gel in which each element is homogeneously mixed, thereby increasing reactivity. If the starting materials cannot be dissolved in pure water, they are dissolved using acid.

[0052] Examples of acids used to dissolve the raw materials include citric acid and oxalic acid, but it is preferable to use oxalic acid from the viewpoint of solubility. For example, when using oxalic acid, it is preferable to use a concentration of 0.5 mol / L or more and 1 mol / L or less. When dissolving, it is preferable to use a temperature of 70°C or more in order to shorten the reaction time.

[0053] If it is difficult to dissolve the raw materials, the reaction can be carried out as a dispersion. In this case, the average particle size of the raw materials contained in the dispersion is preferably 3 μm or less, more preferably 1 μm. After preparing a solution (or dispersion) in which the composition ratio of each compound is adjusted to a predetermined ratio, the solution is heated and stirred while being neutralized with an aqueous ammonia solution to adjust the pH. A gel solution is obtained by adjusting the pH. By setting the pH to 5 or more and 8 or less, it is possible to form a gel that contains each raw material homogeneously, and this makes it possible to obtain a dry gel that has good reactivity when fired.

[0054] Next, the gel liquid is heated to near the boiling point to evaporate the water and proceed with gelation. After gelation, the water is further evaporated and dried to obtain a dry gel. During gelation and drying, the entire amount of the solution can be evaporated and concentrated to obtain a dry gel, but it is more preferable to use a spray dryer, since the particle size after drying can be made smaller. The dry gel produced by evaporating and concentrating the entire amount of the solution is preferably pulverized before firing to reduce the average particle size to 10 μm or less, more preferably 5 μm or less. This allows the particle size after firing to be reduced. The obtained dry gel is fired.

[0055] The dried gel is pre-baked at 200°C to 500°C for 1 hour to 10 hours. This makes it possible to eliminate excess organic components, thereby increasing the reactivity during the main baking.

[0056] The firing temperature is preferably 700°C or higher and 1100°C or lower, more preferably 700°C or higher and 1000°C or lower. The firing time is preferably 1 hour or higher and 10 hours or lower. Since the sol-gel method is a wet method, firing can be performed at a lower temperature and in a shorter time than the solid-phase reaction method. By firing in this temperature range, it is possible to obtain the desired phase while suppressing the sublimation of tungsten. After firing, the mixture is cooled.

[0057] The powder after firing may have a high average particle size due to the formation of aggregates. In this case, it is preferable to adjust the predetermined average particle size by pulverization. When adding a trace amount of the above-mentioned element to an active material containing a complex oxide synthesized by a sol-gel method, for example, prior to firing, an oxide of the element to be added is mixed with a powder sample obtained by pulverizing a dry gel. By performing firing in a state in which the oxide is mixed, an active material containing the additive element together with the complex oxide, or an active material containing a substituted complex oxide in which the additive element is introduced into the crystal structure of the complex oxide can be obtained. In addition, when an oxide of an element that exerts an effect as a sintering aid is added, the firing temperature can be lowered.

[0058] <Various measurement methods> The measurement methods for the active material will be described below. Specifically, the confirmation of the composite oxide, the measurement of the average particle size of the active material particles, and the measurement of the specific surface area of ​​the active material will be described.

[0059] When the active material contained in the electrode of a battery is used as a sample, the measurement sample is prepared by pre-treating it as follows. First, the battery is brought to a fully discharged state (state of charge: SOC 0%). Next, the battery is disassembled in a glove box under an argon atmosphere, and the electrodes are removed. The removed electrodes are then washed using a solvent such as ethyl methyl carbonate. Further processing is performed for each measurement to prepare a sample in an appropriate form.

[0060] (Confirmation of complex oxides) The active material according to the embodiment has the general formula Li a Ti b Nb2W c O 2b+3c+5+δ and that the crystal structure is at least one of a monoclinic structure and an orthorhombic structure, can be confirmed by combining wide-angle X-ray diffraction (XRD) with inductively coupled plasma (ICP) optical emission spectrometry and inert gas dissolution-infrared absorption spectrometry. The crystal structure can be determined by wide-angle XRD, and the elemental composition can be determined by ICP optical emission spectrometry and inert gas dissolution-infrared absorption spectrometry.

[0061] The XRD measurement is carried out as follows. First, the active material particles are thoroughly pulverized to obtain a powdered sample. The average particle size of the powdered sample is preferably 20 μm or less. This average particle size can be determined by a laser diffraction particle size distribution analyzer.

[0062] Next, the powdered sample is filled into the holder of a glass sample plate, and the surface is made flat. For example, the glass sample plate may have a holder depth of 0.2 mm.

[0063] Next, the glass sample plate is placed in a powder X-ray diffractometer, and the XRD spectrum is measured using Cu-Kα radiation. Specific measurement conditions are, for example, as follows: X-ray diffraction equipment: Rigaku SmartLab X-ray source: CuKα ray Output: 40kV, 200mA Package measurement name: General purpose measurement (concentration method) Incident parallel slit aperture angle: 5° Incident longitudinal limiting slit length: 10 mm Photoreceptor PSA: None Receiving parallel slit aperture angle: 5° Monochromatization method: Kβ filter method Measurement mode: Continuous Entrance slit width: 0.5° Receiving slit width: 20mm Measurement range (2θ): 5~70° Sampling width (2θ): 0.01° Scan speed: 1°~20° / min.

[0064] In this manner, an XRD spectrum of the active material is obtained. In this XRD spectrum, the horizontal axis indicates the angle of incidence (2θ) and the vertical axis indicates the diffraction intensity (cps). The scan speed can be adjusted within a range such that the count number of the main peak of the XRD spectrum is 50,000 or more and 150,000 or less.

[0065] When the active material contained in a battery electrode is used as a sample, the electrode after cleaning obtained by carrying out the above-mentioned pretreatment is cut into a piece having an area approximately equal to the area of ​​the glass sample plate holder to prepare a measurement sample.

[0066] Next, the obtained measurement sample is directly attached to a glass holder and subjected to XRD measurement. Next, materials other than the active material that may be contained in the electrode, such as a current collector, a conductive agent, and a binder, are measured using XRD to grasp the XRD pattern derived from them. Next, if there is a peak that is thought to be derived from the active material in the measurement sample and a peak of the other material overlapping, the peak of the material other than the active material is separated. In this way, the XRD spectrum of the active material is obtained.

[0067] In order to confirm whether the crystal structure of the measured sample belongs to either the monoclinic or orthorhombic crystal structure described above, the Rietveld method is used. For example, RIETAN-FP is used as an analysis program, and the reliability factor R wp The value of the peaks is at least 20% or less, more preferably 15% or less. At this time, if there is a peak containing impurities and it overlaps with the phase to be analyzed, the analysis accuracy may be deteriorated. In such a case, it is preferable to perform an analysis in which the portion that clearly overlaps with the peaks derived from impurities is excluded from the analysis range. However, this is not the case when the sample contains materials other than the active material according to the embodiment, when the orientation of the sample is extremely high, or when coarse particles are mixed in, since the intensity ratio changes, and the structure is confirmed by confirming that there is no inconsistency in the positions and relative intensities of all peaks attributed to the crystal structure. In addition, when the spectrum intensity is low and the background intensity is low, R wp The reliability factor does not have any meaning in its absolute value, but rather has meaning in judging the relative quality of the fitting under certain measurement conditions.

[0068] The analytical method using RIETAN-FP is explained in detail, for example, in Chapter 9, "Let's try using RIETAN-FP," of the first edition of "Practicalities of Powder X-Ray Analysis" edited by Nakai Izumi and Izumi Fujio (2002, edited by the X-Ray Analysis Research Forum of the Japan Society for Analytical Chemistry, Asakura Publishing).

[0069] RIETAN-FP is a Rietveld analysis program that is distributed free of charge (as of August 2023) on the Internet at https: / / jp-minerals.org / rietan / .

[0070] The content of each element in the active material particles contained in the sample can be confirmed by ICP atomic emission spectrometry for metal elements, and quantitative determination of oxygen element can be performed by inert gas dissolution-infrared absorption spectroscopy, but precise quantification is difficult.

[0071] The active material particles contained in the electrode are subjected to the above-mentioned pretreatment, and then further subjected to the following treatment. From the washed electrode, a member containing active material (for example, the active material-containing layer described in the second embodiment) is peeled off, for example, from the current collector of the electrode. The part peeled off from the electrode is heated in air for a short time (about 1 hour at 500°C) to burn off unnecessary parts such as the binder and conductive agent. Thereafter, the content of each element can be quantified by performing ICP emission spectrometry or the like.

[0072] (Measurement of average particle size) The average primary particle size of the active material can be determined by observation using a scanning electron microscope (SEM). Specifically, the average primary particle size determined by SEM observation can be calculated by the following method.

[0073] First, the length of the longest axis and the length of the shortest axis are measured for the primary particles in the SEM image obtained by SEM observation, and the arithmetic mean of these is taken as the primary particle diameter. This measurement of the primary particle diameter is performed for 100 randomly selected particles, and the average value of these is taken as the average primary particle diameter.

[0074] The average secondary particle diameter of the active material can be determined from the particle size distribution measured using a laser diffraction particle size distribution measuring device. The sample used for this particle size distribution measurement is a dispersion diluted with N-methyl-2-pyrrolidone so that the concentration of the active material is 0.1% by mass to 1% by mass. The particle diameter at which the volumetric integrated value is 50% in the obtained particle size distribution is defined as the average secondary particle diameter.

[0075] (BET specific surface area measurement) The BET specific surface area of ​​the active material particles can be determined by the following method.

[0076] First, 4 g of active material is collected as a sample. Next, the evaluation cell of the measuring device is dried under reduced pressure at a temperature of 100°C or higher for 15 hours to perform a degassing process. For example, a 1 / 2 inch cell can be used as the evaluation cell. Next, the sample is placed in the measuring device. For example, Shimadzu Micromeritics Tristar II 3020 can be used as the measuring device. Next, in nitrogen gas at 77K (boiling point of nitrogen), the nitrogen gas pressure P (mmHg) is gradually increased while measuring the nitrogen gas adsorption amount (mL / g) of the sample for each pressure P. Next, the pressure P (mmHg) is divided by the saturated vapor pressure P0 (mmHg) of nitrogen gas to obtain a relative pressure P / P0, and the nitrogen gas adsorption amount for each relative pressure P / P0 is plotted to obtain an adsorption isotherm. Next, a BET plot is calculated from this nitrogen adsorption isotherm and the BET formula, and the specific surface area is obtained using this BET plot. Note that the BET multipoint method is used to calculate the BET plot.

[0077] (Cs-STEM image observation method) Regarding the structures of FIGS. 1 and 2, it is also possible to confirm them by directly observing the fine structures. The observation can be carried out by observation using the high angle annular dark-field (HAADF) method with a scanning transmission electron microscope (STEM). From the viewpoint of improving the measurement resolution, it is preferable to use spherical aberration correction. By acquiring an atomic image (10 nm × 10 nm) from the direction perpendicular to the ReO3-type block (the direction viewed from the b-axis in FIGS. 1 and 2) and confirming the positional relationship of the metal elements constituting the ReO3 block, the structure can be verified.

[0078] The active material according to the first embodiment is a general formula Li a Ti b Nb2W c O 2b+3c+5+δ which contains a composite oxide represented by 0 ≦ a ≦ b + 3c + 4, 0 < b < 2, 0 < c < 2, 1.9b + 2.85c + 4.75 ≦ δ ≦ 2.1b + 3.15c + 5.25, and the crystal structure of the composite oxide is at least one of a monoclinic structure and an orthorhombic structure. With such a configuration, the electrode using the above composite oxide as the electrode active material has a high capacity per mass. Also, the secondary battery and the battery pack using the above composite oxide as the electrode active material have a high capacity per mass. That is, the active material according to the embodiment exhibits a high capacity.

[0079] [Second Embodiment] According to the second embodiment, an electrode is provided. The electrode according to the second embodiment contains the active material according to the first embodiment. This electrode can be a battery electrode containing the active material according to the first embodiment as a battery active material. The electrode as a battery electrode can be, for example, a negative electrode containing the active material according to the first embodiment as a negative electrode active material. Alternatively, the electrode can be a positive electrode containing the active material according to the first embodiment as a positive electrode active material.

[0080] The electrode according to the second embodiment may include a current collector and an active material-containing layer. The active material-containing layer may be formed on one or both sides of the current collector. The active material-containing layer may include an active material and, optionally, a conductive agent and a binder.

[0081] The active material-containing layer may contain the active material according to the first embodiment alone, or may contain two or more types of active materials according to the first embodiment. Furthermore, it may contain a mixture of one or more types of active materials according to the first embodiment and one or more types of other active materials. It is desirable that the content ratio of the active material according to the first embodiment to the total mass of the active material according to the first embodiment and the other active materials is 10 mass % or more and 100 mass % or less.

[0082] For example, when the active material according to the first embodiment is contained as a negative electrode active material, examples of other active materials include lithium titanate having a ramsdellite structure (e.g., Li 2+x Ti3O7, 0≦x≦3), lithium titanates with spinel structure (e.g., Li 4+x Ti5O 12 , 0≦x≦3), monoclinic titanium dioxide (TiO2), anatase titanium dioxide, rutile titanium dioxide, hollandite titanium composite oxide, orthorhombic titanium-containing composite oxide, and monoclinic niobium titanium composite oxide, niobium oxide, niobium titanium oxide, niobium molybdenum composite oxide, and niobium tungsten composite oxide.

[0083] As an example of the above-mentioned orthorhombic titanium-containing composite oxide, Li 2+e M2 2-f Ti 6-g M3 h O 14+σHere, M2 is at least one selected from the group consisting of Sr, Ba, Ca, Mg, Na, Cs, Rb, and K. M3 is at least one selected from the group consisting of Zr, Sn, V, Nb, Ta, Mo, W, Y, Fe, Co, Cr, Mn, Ni, and Al. The subscripts in the composition formula are 0≦e≦6, 0≦f<2, 0≦g<6, 0≦h<6, and -0.5≦σ≦0.5. Specific examples of orthorhombic titanium-containing composite oxides include Li 2+e Na2Ti6O 14 (0≦e≦6).

[0084] As an example of the monoclinic niobium titanium composite oxide, Li x Ti 1-y M4 y Nb 2-z M5 z O 7+δ Here, M4 is at least one selected from the group consisting of Zr, Si, and Sn. M5 is at least one selected from the group consisting of V, Ta, and Bi. The subscripts in the composition formula are 0≦x≦5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3. Specific examples of monoclinic niobium titanium composite oxides include Li x Examples include Nb2TiO7 (0≦x≦5).

[0085] Another example of monoclinic niobium titanium composite oxide is Li x Ti 1-y M6 y+z Nb 2-z O 7-δ Here, M6 is at least one selected from the group consisting of Mg, Fe, Ni, Co, W, Ta, and Mo. Each subscript in the composition formula is 0≦x<5, 0≦y<1, 0≦z<2, and -0.3≦δ≦0.3.

[0086] The conductive agent is blended to improve the current collecting performance and to suppress the contact resistance between the active material and the current collector. Examples of the conductive agent include carbonaceous materials such as vapor grown carbon fiber (VGCF), carbon black such as acetylene black, graphite, carbon nanotubes, and carbon nanofibers. One of these may be used as the conductive agent, or two or more may be used in combination as the conductive agent. Alternatively, instead of using the conductive agent, a carbon coat or an electronically conductive inorganic material coat may be applied to the surface of the active material particles. In addition, the current collecting performance of the active material-containing layer can be improved by using the conductive agent and coating the active material surface with carbon or a conductive material.

[0087] The binder is blended to fill the gaps between the dispersed active materials and to bind the active materials and the current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, styrene-butadiene rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.

[0088] The mixing ratio of the active material, conductive agent, and binder in the active material-containing layer can be appropriately changed depending on the application of the electrode. For example, when the electrode is used as a negative electrode of a secondary battery, it is preferable to mix the active material (negative electrode active material), conductive agent, and binder at a ratio of 68% by mass or more and 96% by mass or less, 2% by mass or more and 30% by mass or less, and 2% by mass or more and 30% by mass or less, respectively. By making the amount of the conductive agent 2% by mass or more, the current collection performance of the active material-containing layer can be improved. In addition, by making the amount of the binder 2% by mass or more, the binding property between the active material-containing layer and the current collector becomes sufficient, and excellent cycle performance can be expected. On the other hand, it is preferable to make the conductive agent and the binder 30% by mass or less, respectively, in order to increase the capacity.

[0089] When the surface of the active material is coated with carbon or a conductive material, the amount of the coating material can be considered to be included in the amount of the conductive material. The amount of carbon or conductive material coated is preferably 0.5% by mass or more and 5% by mass or less. If the amount of coating is within this range, the current collection performance and the electrode density can be improved.

[0090] The current collector is made of a material that is electrochemically stable at the potential at which lithium (Li) is inserted and removed from the active material. For example, when the active material is used as a negative electrode active material, the current collector is preferably made of copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing one or more elements selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The thickness of the current collector is preferably 5 μm or more and 20 μm or less. A current collector having such a thickness can balance the strength and weight of the electrode.

[0091] The current collector may also include a portion on the surface of which no active material-containing layer is formed, and this portion can function as a current collecting tab.

[0092] The electrode can be produced, for example, by the following method. First, an active material, a conductive agent, and a binder are suspended in a solvent to prepare a slurry. This slurry is applied to one or both sides of a current collector. Next, the applied slurry is dried to obtain a laminate of an active material-containing layer and a current collector. After that, the laminate is pressed. In this manner, an electrode is produced.

[0093] Alternatively, the electrode may be prepared by the following method: first, the active material, the conductive agent, and the binder are mixed to obtain a mixture, then the mixture is formed into pellets, and then the pellets are placed on a current collector to obtain an electrode.

[0094] The electrode according to the second embodiment contains the active material according to the first embodiment, and therefore the electrode according to the second embodiment can realize a secondary battery with a high capacity per mass.

[0095] [Third embodiment] According to the third embodiment, a secondary battery including a negative electrode, a positive electrode, and an electrolyte is provided. This secondary battery includes the electrode according to the second embodiment as the negative electrode, the positive electrode, or both the negative electrode and the positive electrode. That is, the secondary battery according to the third embodiment includes an electrode including the active material according to the first embodiment as a battery active material as a battery electrode. A secondary battery according to a desirable aspect includes an electrode according to the second embodiment as a negative electrode. That is, a secondary battery according to a desirable aspect includes an electrode including the active material according to the first embodiment as a battery active material as a negative electrode. Desired aspects will be described below.

[0096] The secondary battery according to the third embodiment may further include a separator disposed between the positive electrode and the negative electrode. The negative electrode, the positive electrode, and the separator may constitute an electrode group. The electrolyte may be held in the electrode group.

[0097] Moreover, the secondary battery according to the third embodiment can further include an exterior member that houses the electrode group and the electrolyte.

[0098] Furthermore, the secondary battery according to the third embodiment may further include a negative electrode terminal electrically connected to the negative electrode, and a positive electrode terminal electrically connected to the positive electrode.

[0099] The secondary battery according to the third embodiment may be, for example, a lithium secondary battery. The secondary battery includes a non-aqueous electrolyte secondary battery that contains a non-aqueous electrolyte.

[0100] The negative electrode, the positive electrode, the electrolyte, the separator, the exterior member, the negative electrode terminal, and the positive electrode terminal will be described in detail below.

[0101] 1) Negative electrode The negative electrode may include a negative electrode current collector and a negative electrode active material-containing layer. The negative electrode current collector and the negative electrode active material-containing layer may be the current collector and the active material-containing layer that can be included in the electrode according to the second embodiment, respectively. The negative electrode active material-containing layer includes the active material according to the first embodiment as a negative electrode active material.

[0102] Among the details of the negative electrode, those parts that overlap with the details explained in the second embodiment will be omitted.

[0103] The density of the negative electrode active material-containing layer (excluding the current collector) is 1.8 g / cm 3 More than 2.8g / cm 3 A negative electrode having a density of the negative electrode active material-containing layer within this range is excellent in energy density and electrolyte retention. The density of the negative electrode active material-containing layer is preferably 2.1 g / cm or less. 3 More than 2.6g / cm 3 It is more preferable that:

[0104] The negative electrode can be produced, for example, by the same method as that for the electrode according to the second embodiment.

[0105] 2) Positive electrode The positive electrode may include a positive electrode current collector and a positive electrode active material-containing layer. The positive electrode active material-containing layer may be formed on one or both sides of the positive electrode current collector. The positive electrode active material-containing layer may include a positive electrode active material, and optionally a conductive agent and a binder.

[0106] As the positive electrode active material, for example, an oxide or a sulfide can be used. The positive electrode may contain one type of compound alone as the positive electrode active material, or may contain two or more types of compounds in combination. Examples of oxides and sulfides include compounds that can insert and remove Li or Li ions. Depending on the target battery, the active material of the first embodiment may be included.

[0107] Examples of such compounds include manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, and lithium manganese composite oxides (e.g., Lix Mn2O4 or Li x MnO2; 0 < x ≦ 1), lithium nickel composite oxide (e.g., Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxide (e.g., Li x CoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≦ 1, 0 < y < 1), lithium manganese nickel composite oxide having a spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≦ 1, 0 < y < 2), lithium phosphate having an olivine structure (e.g., Li x FePO4; 0 < x ≦ 1, Li x Fe 1-y Mn y PO4; 0 < x ≦ 1, 0 < y ≦ 1, Li x CoPO4; 0 < x ≦ 1), iron sulfate (Fe2(SO4)3), vanadium oxide (e.g., V2O5), and lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≦ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included.

[0108] Among the above, examples of more preferable compounds as the positive electrode active material include lithium manganese composite oxide having a spinel structure (e.g., Li x Mn2O4; 0 < x ≦ 1), lithium nickel composite oxide (e.g., Li x NiO2; 0 < x ≦ 1), lithium cobalt composite oxide (e.g., Li x CoO2; 0 < x ≦ 1), lithium nickel cobalt composite oxide (e.g., Li x Ni 1-y Co yO2; 0 < x ≤ 1, 0 < y < 1), a lithium manganese nickel composite oxide having a spinel structure (e.g., Li x Mn 2-y Ni y O4; 0 < x ≤ 1, 0 < y < 2), a lithium manganese cobalt composite oxide (e.g., Li x Mn y Co 1-y O2; 0 < x ≤ 1, 0 < y < 1), lithium iron phosphate (e.g., Li x FePO4; 0 < x ≤ 1), and a lithium nickel cobalt manganese composite oxide (Li x Ni 1-y-z Co y Mn z O2; 0 < x ≤ 1, 0 < y < 1, 0 < z < 1, y + z < 1) are included. When these compounds are used as the positive electrode active material, the positive electrode potential can be increased.

[0109] When a room temperature molten salt is used as the electrolyte of the battery, it is preferable to use a positive electrode active material containing lithium iron phosphate, Li x VPO4F (0 ≤ x ≤ 1), a lithium manganese composite oxide, a lithium nickel composite oxide, a lithium nickel cobalt composite oxide, or a mixture thereof. Since these compounds have low reactivity with the room temperature molten salt, the cycle life can be improved. Details of the room temperature molten salt will be described later.

[0110] The primary particle size of the positive electrode active material is preferably 100 nm or more and 1 μm or less. A positive electrode active material with a primary particle size of 100 nm or more is easy to handle in industrial production. A positive electrode active material with a primary particle size of 1 μm or less can allow the solid-state diffusion of lithium ions to proceed smoothly.

[0111] The specific surface area of the positive electrode active material is preferably 0.1 m 2 / g or more and 10 m 2 / g or less. A positive electrode active material having a specific surface area of 0.1 m 2 / g or more can sufficiently secure insertion / desorption sites for Li ions. A positive electrode active material with a specific surface area of 10 m 2A positive electrode active material having a specific surface area of ​​100 / g or less is easy to handle in industrial production and can ensure good charge-discharge cycle performance.

[0112] The binder is blended to fill the gaps between the dispersed positive electrode active material and to bind the positive electrode active material and the positive electrode current collector. Examples of the binder include polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine-based rubber, polyacrylic acid compounds, imide compounds, carboxymethyl cellulose (CMC), and salts of CMC. One of these may be used as the binder, or two or more may be used in combination as the binder.

[0113] The conductive agent is blended to improve current collection performance and reduce contact resistance between the positive electrode active material and the positive electrode current collector. Examples of the conductive agent include vapor grown carbon fiber (VGCF), carbon black such as acetylene black, and carbonaceous materials such as graphite. One of these may be used as the conductive agent, or two or more may be combined and used as the conductive agent. The conductive agent may also be omitted.

[0114] In the positive electrode active material-containing layer, the positive electrode active material and the binder are preferably mixed in proportions of 80% by mass to 98% by mass and 2% by mass to 20% by mass, respectively.

[0115] By making the amount of binder 2% by mass or more, sufficient electrode strength can be obtained. In addition, the binder can function as an insulator. Therefore, by making the amount of binder 20% by mass or less, the amount of insulator contained in the electrode is reduced, and the internal resistance can be reduced.

[0116] When a conductive agent is added, the positive electrode active material, the binder, and the conductive agent are preferably mixed in proportions of 77% by mass or more and 95% by mass or less, 2% by mass or more and 20% by mass or less, and 3% by mass or more and 15% by mass or less, respectively.

[0117] By setting the amount of the conductive agent to 3% by mass or more, the above-mentioned effects can be achieved. Also, by setting the amount of the conductive agent to 15% by mass or less, the ratio of the conductive agent in contact with the electrolyte can be reduced. If this ratio is low, decomposition of the electrolyte during high-temperature storage can be reduced.

[0118] The positive electrode current collector is preferably an aluminum foil or an aluminum alloy foil containing one or more elements selected from the group consisting of Mg, Ti, Zn, Ni, Cr, Mn, Fe, Cu, and Si.

[0119] The thickness of the aluminum foil or aluminum alloy foil is preferably 5 μm or more and 20 μm or less, more preferably 15 μm or less. The purity of the aluminum foil is preferably 99 mass% or more. The content of transition metals such as iron, copper, nickel, and chromium contained in the aluminum foil or aluminum alloy foil is preferably 1 mass% or less.

[0120] The positive electrode current collector may also include a portion on the surface of which the positive electrode active material-containing layer is not formed, and this portion can function as a positive electrode current collecting tab.

[0121] The positive electrode can be produced, for example, by using a positive electrode active material in the same manner as in the electrode according to the second embodiment.

[0122] 3) Electrolyte The electrolyte may be, for example, a liquid nonaqueous electrolyte or a gel nonaqueous electrolyte. The liquid nonaqueous electrolyte is prepared by dissolving an electrolyte salt as a solute in an organic solvent. The concentration of the electrolyte salt is preferably 0.5 mol / L or more and 2.5 mol / L or less.

[0123] Examples of the electrolyte salt include lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), and lithium salts such as lithium bistrifluoromethylsulfonylimide (LiN(CF3SO2)2), lithium bis(fluorosulfonyl)imide (LiN(SO2F)2:LiFSI), and mixtures thereof. The electrolyte salt is preferably one that is difficult to oxidize even at high potentials, and LiPF6 is most preferred.

[0124] Examples of organic solvents include cyclic carbonates such as propylene carbonate (PC), ethylene carbonate (EC), and vinylene carbonate (VC); chain carbonates such as diethyl carbonate (DEC), dimethyl carbonate (DMC), and methyl ethyl carbonate (MEC); cyclic ethers such as tetrahydrofuran (THF), 2-methyl tetrahydrofuran (2MeTHF), and dioxolane (DOX); chain ethers such as dimethoxy ethane (DME), and diethoxy ethane (DEE); γ-butyrolactone (GBL), acetonitrile (AN), and sulfolane (SL). These organic solvents can be used alone or as a mixed solvent.

[0125] The gelled non-aqueous electrolyte is prepared by combining a liquid non-aqueous electrolyte with a polymeric material, such as polyvinylidene fluoride (PVdF), polyacrylonitrile (PAN), polyethylene oxide (PEO), or a mixture thereof.

[0126] Alternatively, in addition to liquid nonaqueous electrolytes and gel nonaqueous electrolytes, room temperature molten salts containing lithium ions (ionic melts), polymer solid electrolytes, inorganic solid electrolytes, and the like may be used as the nonaqueous electrolyte.

[0127] Room temperature molten salts (ionic melts) refer to organic salts consisting of a combination of organic cations and anions that can exist as a liquid at room temperature (15°C or higher and 25°C or lower). Room temperature molten salts include room temperature molten salts that exist as a liquid by themselves, room temperature molten salts that become liquid when mixed with an electrolyte salt, room temperature molten salts that become liquid when dissolved in an organic solvent, and mixtures of these. In general, the melting point of room temperature molten salts used in secondary batteries is 25°C or lower. In addition, organic cations generally have a quaternary ammonium skeleton.

[0128] The polymer solid electrolyte is prepared by dissolving an electrolyte salt in a polymer material and solidifying it.

[0129] The inorganic solid electrolyte is a solid material that has Li-ion conductivity.

[0130] Alternatively, instead of the non-aqueous electrolyte, a liquid aqueous electrolyte or a gel aqueous electrolyte can be used as the electrolyte. The liquid aqueous electrolyte is prepared by dissolving, for example, the above-mentioned electrolyte salt as a solute in an aqueous solvent. The gel aqueous electrolyte is prepared by compounding the liquid aqueous electrolyte with the above-mentioned polymer material. As the aqueous solvent, a solution containing water can be used. The solution containing water may be pure water or a mixed solvent of water and an organic solvent.

[0131] 4) Separator The separator is formed, for example, from a porous film containing polyethylene (PE), polypropylene (PP), cellulose, or polyvinylidene fluoride (PVdF), or a synthetic resin nonwoven fabric. From the viewpoint of safety, it is preferable to use a porous film formed from polyethylene or polypropylene. This is because these porous films melt at a certain temperature and are capable of cutting off electric current.

[0132] 5) Exterior materials The exterior member may be, for example, a container made of a laminate film or a metal container. The thickness of the laminate film is, for example, 0.5 mm or less, and preferably 0.2 mm or less.

[0133] The laminate film is a multi-layer film including a plurality of resin layers and a metal layer interposed between the resin layers. The resin layers include polymeric materials such as polypropylene (PP), polyethylene (PE), nylon, and polyethylene terephthalate (PET). The metal layer is preferably made of aluminum foil or aluminum alloy foil for weight reduction. The laminate film can be molded into the shape of the exterior member by sealing it by heat fusion.

[0134] The thickness of the wall of the metal container is, for example, 1 mm or less, more preferably 0.5 mm or less, and even more preferably 0.2 mm or less.

[0135] The metal container is made of, for example, aluminum or an aluminum alloy. The aluminum alloy preferably contains elements such as magnesium, zinc, and silicon. When the aluminum alloy contains a transition metal such as iron, copper, nickel, and chromium, the content of the transition metal is preferably 1 mass % or less.

[0136] The shape of the exterior member is not particularly limited. The shape of the exterior member may be, for example, flat (thin), rectangular, cylindrical, coin, or button. The exterior member can be appropriately selected depending on the battery dimensions and the application of the battery.

[0137] 6) Negative terminal The negative electrode terminal can be formed from a material that is electrochemically stable at the Li insertion / extraction potential of the above-mentioned negative electrode active material and has electrical conductivity. Specifically, the material of the negative electrode terminal can be copper, nickel, stainless steel, or aluminum, or an aluminum alloy containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The material of the negative electrode terminal is preferably aluminum or an aluminum alloy. The negative electrode terminal is preferably made of the same material as the negative electrode current collector in order to reduce the contact resistance with the negative electrode current collector.

[0138] 7) Positive terminal The positive electrode terminal can be formed from a material that is electrically stable and conductive in a potential range of 3 V to 4.5 V (vs. Li / Li+) relative to the redox potential of lithium. Examples of the material for the positive electrode terminal include aluminum and aluminum alloys containing at least one element selected from the group consisting of Mg, Ti, Zn, Mn, Fe, Cu, and Si. The positive electrode terminal is preferably formed from the same material as the positive electrode current collector in order to reduce the contact resistance with the positive electrode current collector.

[0139] Above, the embodiment including the electrode according to the second embodiment as the negative electrode has been described. In the embodiment of the secondary battery according to the third embodiment including the electrode according to the second embodiment as the positive electrode, the negative electrode which is the counter electrode thereof can be, for example, the following counter electrode. At least one electrode selected from lithium metal, lithium metal alloy, graphite, silicon, silicon oxide, tin oxide, silicon, tin, and other alloys can be used as the negative electrode. A material that does not contain Li in the active material can be used as the negative electrode by pre-doping with Li element.

[0140] In an embodiment including the electrode according to the second embodiment as a positive electrode, details of the positive electrode overlap with those described in the second embodiment, and therefore will be omitted.

[0141] Next, the secondary battery according to the third embodiment will be described more specifically with reference to the drawings.

[0142] Fig. 3 is a cross-sectional view that illustrates an example of a secondary battery according to a third embodiment of the present invention, and Fig. 4 is an enlarged cross-sectional view of part A of the secondary battery illustrated in Fig. 3.

[0143] The secondary battery 100 shown in Figures 3 and 4 includes an electrode group 1 shown in Figure 4, a bag-shaped exterior member 2 shown in Figures 3 and 4, and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the bag-shaped exterior member 2. The electrolyte (not shown) is held in the electrode group 1.

[0144] The bag-shaped exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0145] As shown in Fig. 3, the electrode group 1 is a flat wound-type electrode group. As shown in Fig. 4, the flat wound-type electrode group 1 includes a negative electrode 3, a separator 4, and a positive electrode 5. The separator 4 is interposed between the negative electrode 3 and the positive electrode 5.

[0146] The negative electrode 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b. In the negative electrode 3, in a portion located at the outermost shell of the wound-type electrode group 1, the negative electrode active material-containing layer 3b is formed only on the inner surface side of the negative electrode current collector 3a as shown in Fig. 5. In the other portions of the negative electrode 3, the negative electrode active material-containing layer 3b is formed on both sides of the negative electrode current collector 3a.

[0147] The positive electrode 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b formed on both sides of the positive electrode current collector 5a.

[0148] As shown in FIG. 3, the negative electrode terminal 6 and the positive electrode terminal 7 are located near the outer peripheral end of the wound electrode group 1. The negative electrode terminal 6 is connected to a portion located at the outermost shell of the negative electrode current collector 3a. The positive electrode terminal 7 is connected to a portion located at the outermost shell of the positive electrode current collector 5a. The negative electrode terminal 6 and the positive electrode terminal 7 extend to the outside from an opening of the bag-shaped exterior member 2. A thermoplastic resin layer is provided on the inner surface of the bag-shaped exterior member 2, and the opening is closed by heat sealing.

[0149] The secondary battery according to the third embodiment is not limited to the secondary battery having the configuration shown in FIGS. 3 and 4, but may be a battery having the configuration shown in FIGS.

[0150] Fig. 5 is a partially cutaway perspective view showing typically another example of the secondary battery according to embodiment 3. Fig. 6 is an enlarged cross-sectional view of part B of the secondary battery shown in Fig. 5.

[0151] The secondary battery 100 shown in Figures 6 and 7 includes an electrode group 1 shown in Figures 6 and 7, an exterior member 2 shown in Figure 6, and an electrolyte (not shown). The electrode group 1 and the electrolyte are housed in the exterior member 2. The electrolyte is held in the electrode group 1.

[0152] The exterior member 2 is made of a laminate film including two resin layers and a metal layer interposed between them.

[0153] The electrode group 1 is a laminated type electrode group, as shown in Fig. 6. The laminated type electrode group 1 has a structure in which negative electrodes 3 and positive electrodes 5 are alternately laminated with separators 4 interposed therebetween.

[0154] The electrode group 1 includes a plurality of negative electrodes 3. Each of the plurality of negative electrodes 3 includes a negative electrode current collector 3a and a negative electrode active material-containing layer 3b supported on both sides of the negative electrode current collector 3a. The electrode group 1 also includes a plurality of positive electrodes 5. Each of the plurality of positive electrodes 5 includes a positive electrode current collector 5a and a positive electrode active material-containing layer 5b supported on both sides of the positive electrode current collector 5a.

[0155] The negative electrode current collector 3a of each negative electrode 3 includes a portion 3c on one side of which the negative electrode active material-containing layer 3b is not supported on any surface. This portion 3c serves as a negative electrode current collector tab. As shown in FIG. 6, the portion 3c serving as the negative electrode current collector tab does not overlap with the positive electrode 5. In addition, the multiple negative electrode current collector tabs (portions 3c) are electrically connected to a strip-shaped negative electrode terminal 6. The tip of the strip-shaped negative electrode terminal 6 is pulled out to the outside of the exterior member 2.

[0156] Although not shown, the positive electrode current collector 5a of each positive electrode 5 includes a portion on one side where the positive electrode active material-containing layer 5b is not supported on any surface. This portion serves as a positive electrode current collector tab. The positive electrode current collector tab does not overlap with the negative electrode 3, similar to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is located on the opposite side of the electrode group 1 to the negative electrode current collector tab (portion 3c). The positive electrode current collector tab is electrically connected to a strip-shaped positive electrode terminal 7. The tip of the strip-shaped positive electrode terminal 7 is located on the opposite side to the negative electrode terminal 6, and is drawn out to the outside of the exterior member 2.

[0157] The secondary battery according to the third embodiment includes the electrode according to the second embodiment. That is, the secondary battery according to the third embodiment includes the electrode including the active material according to the first embodiment. Therefore, the secondary battery according to the third embodiment has a high capacity per mass.

[0158] [Fourth embodiment] According to a fourth embodiment, there is provided a battery pack. The battery pack according to the fourth embodiment includes a plurality of secondary batteries according to the third embodiment.

[0159] In the battery pack according to the fourth embodiment, the individual cells may be electrically connected in series or parallel, or may be arranged in a combination of series and parallel connections.

[0160] Next, an example of a battery pack according to a fourth embodiment will be described with reference to the drawings.

[0161] Fig. 7 is a perspective view showing an example of a battery pack according to the fourth embodiment. The battery pack 200 shown in Fig. 7 includes five cells 100a to 100e, four bus bars 21, a positive electrode lead 22, and a negative electrode lead 23. Each of the five cells 100a to 100e is a secondary battery according to the third embodiment.

[0162] The bus bar 21 connects, for example, the negative electrode terminal 6 of one cell 100a and the positive electrode terminal 7 of the adjacent cell 100b. In this way, the five cells 100 are connected in series by the four bus bars 21. That is, the battery pack 200 in FIG. 7 is a five-series battery pack. Although no example is shown, in a battery pack including a plurality of cells electrically connected in parallel, for example, the plurality of negative electrode terminals are connected to each other by a bus bar and the plurality of positive electrode terminals are connected to each other by a bus bar, so that the plurality of cells are electrically connected to each other.

[0163] The positive electrode terminal 7 of at least one of the five cells 100a to 100e is electrically connected to a positive electrode lead 22 for external connection. Also, the negative electrode terminal 6 of at least one of the five cells 100a to 100e is electrically connected to a negative electrode lead 23 for external connection.

[0164] The battery pack according to the fourth embodiment includes the secondary battery according to the third embodiment, and therefore has a high capacity per mass.

[0165] [Fifth embodiment] According to a fifth embodiment, there is provided a battery pack. The battery pack includes the battery assembly according to the fourth embodiment. The battery pack may include a single secondary battery according to the third embodiment, instead of the battery assembly according to the fourth embodiment.

[0166] The battery pack according to the fifth embodiment may further include a protection circuit. The protection circuit has a function of controlling charging and discharging of the secondary battery. Alternatively, a circuit included in a device (e.g., electronic device, automobile, etc.) that uses the battery pack as a power source may be used as the protection circuit for the battery pack.

[0167] The battery pack according to the fifth embodiment may further include an external terminal for current flow. The external terminal for current flow is for outputting current from the secondary battery to the outside and / or for inputting current from the outside to the secondary battery. In other words, when the battery pack is used as a power source, current is supplied to the outside through the external terminal for current flow. When the battery pack is charged, a charging current (including regenerative energy from the power of an automobile or the like) is supplied to the battery pack through the external terminal for current flow.

[0168] Next, an example of a battery pack according to a fifth embodiment will be described with reference to the drawings.

[0169] Fig. 8 is an exploded perspective view showing an example of a battery pack according to a fifth embodiment of the present invention, and Fig. 9 is a block diagram showing an example of an electric circuit of the battery pack shown in Fig. 8.

[0170] The battery pack 300 shown in Figs. 8 and 9 includes a container 31, a lid 32, a protective sheet 33, a battery pack 200, a printed wiring board 34, wiring 35, and an insulating plate (not shown).

[0171] 8 is a bottomed, square container having a rectangular bottom. The container 31 is configured to be capable of housing a protective sheet 33, a battery pack 200, a printed wiring board 34, and wiring 35. The lid 32 has a rectangular shape. The lid 32 covers the container 31 to house the battery pack 200 and the like. Although not shown, the container 31 and the lid 32 are provided with openings or connection terminals for connection to an external device or the like.

[0172] The battery pack 200 includes a plurality of cells 100, a positive electrode lead 22, a negative electrode lead 23, and an adhesive tape 24.

[0173] At least one of the plurality of unit cells 100 is a secondary battery according to the third embodiment. Each of the plurality of unit cells 100 is electrically connected in series as shown in FIG. 10. The plurality of unit cells 100 may be electrically connected in parallel, or may be connected in a combination of series and parallel connections. When the plurality of unit cells 100 are connected in parallel, the battery capacity is increased compared to when they are connected in series.

[0174] The adhesive tape 24 fastens the plurality of unit cells 100. The plurality of unit cells 100 may be fixed using heat shrink tape instead of the adhesive tape 24. In this case, the protective sheets 33 are disposed on both side surfaces of the battery pack 200, the heat shrink tape is wrapped around the battery pack 200, and the heat shrink tape is then thermally shrunk to bind the plurality of unit cells 100 together.

[0175] One end of the positive electrode lead 22 is connected to the battery pack 200. One end of the positive electrode lead 22 is electrically connected to the positive electrode of one or more cells 100. One end of the negative electrode lead 23 is connected to the battery pack 200. One end of the negative electrode lead 23 is electrically connected to the negative electrode of one or more cells 100.

[0176] The printed wiring board 34 is disposed along one of the short side surfaces of the inner surface of the container 31. The printed wiring board 34 includes a positive connector 342, a negative connector 343, a thermistor 345, a protection circuit 346, wiring 342a and 343a, an external terminal 350 for supplying electricity, a positive wiring (positive wiring) 348a, and a negative wiring (negative wiring) 348b. One main surface of the printed wiring board 34 faces one side of the battery pack 200. An insulating plate (not shown) is interposed between the printed wiring board 34 and the battery pack 200.

[0177] The other end 22a of the positive electrode lead 22 is electrically connected to the positive electrode connector 342. The other end 23a of the negative electrode lead 23 is electrically connected to the negative electrode connector 343.

[0178] The thermistor 345 is fixed to one main surface of the printed wiring board 34. The thermistor 345 detects the temperature of each of the cells 100, and transmits a detection signal to the protection circuit 346.

[0179] The external terminal 350 for current supply is fixed to the other main surface of the printed wiring board 34. The external terminal 350 for current supply is electrically connected to a device present outside the battery pack 300. The external terminal 350 for current supply includes a positive terminal 352 and a negative terminal 353.

[0180] The protection circuit 346 is fixed to the other main surface of the printed wiring board 34. The protection circuit 346 is connected to the positive terminal 352 via a positive wiring 348a. The protection circuit 346 is connected to the negative terminal 353 via a negative wiring 348b. The protection circuit 346 is also electrically connected to the positive electrode connector 342 via a wiring 342a. The protection circuit 346 is electrically connected to the negative electrode connector 343 via a wiring 343a. Furthermore, the protection circuit 346 is electrically connected to each of the plurality of single cells 100 via the wiring 35.

[0181] The protective sheet 33 is disposed on both inner surfaces in the long side direction of the container 31 and on the inner surface in the short side direction that faces the printed wiring board 34 via the battery pack 200. The protective sheet 33 is made of, for example, resin or rubber.

[0182] The protection circuit 346 controls charging and discharging of the multiple cells 100. In addition, the protection circuit 346 cuts off electrical connection between the protection circuit 346 and external terminals 350 (positive terminal 352, negative terminal 353) for supplying electricity to an external device, based on a detection signal transmitted from the thermistor 345, or a detection signal transmitted from each of the cells 100 or the battery pack 200.

[0183] An example of the detection signal transmitted from the thermistor 345 is a signal that detects that the temperature of the cell 100 is equal to or higher than a predetermined temperature. An example of the detection signal transmitted from each cell 100 or the battery pack 200 is a signal that detects overcharging, overdischarging, and overcurrent of the cell 100. When detecting overcharging or the like for each cell 100, the battery voltage may be detected, or the positive electrode potential or the negative electrode potential may be detected. In the latter case, a lithium electrode used as a reference electrode is inserted into each cell 100.

[0184] The protection circuit 346 may be a circuit included in a device (such as an electronic device or an automobile) that uses the battery pack 300 as a power source.

[0185] As described above, the battery pack 300 includes the external terminal 350 for current supply. Therefore, the battery pack 300 can output a current from the assembled battery 200 to an external device and input a current from the external device to the assembled battery 200 via the external terminal 350 for current supply. In other words, when the battery pack 300 is used as a power source, the current from the assembled battery 200 is supplied to the external device through the external terminal 350 for current supply. When the battery pack 300 is charged, a charging current from the external device is supplied to the battery pack 300 through the external terminal 350 for current supply. When the battery pack 300 is used as an in-vehicle battery, regenerative energy of the vehicle's power can be used as the charging current from the external device.

[0186] The battery pack 300 may include a plurality of assembled batteries 200. In this case, the assembled batteries 200 may be connected in series, in parallel, or in a combination of series and parallel connections. The printed wiring board 34 and the wiring 35 may be omitted. In this case, the positive electrode lead 22 and the negative electrode lead 23 may be used as a positive terminal 352 and a negative terminal 353, respectively, of the external terminal 350 for current supply.

[0187] Such a battery pack is used in applications that require excellent cycle performance, for example, when a large current is drawn. Specifically, the battery pack is used, for example, as a power source for electronic devices, a stationary battery, or an on-board battery for various vehicles. An example of the electronic device is a digital camera. The battery pack is particularly suitable for use as an on-board battery.

[0188] The battery pack according to the fifth embodiment includes the secondary battery according to the third embodiment or the battery pack according to the fourth embodiment, and therefore the battery pack according to the embodiments has a high capacity per volume.

[0189] [Sixth embodiment] According to a sixth embodiment, a vehicle is provided. The vehicle is equipped with the battery pack according to the fifth embodiment.

[0190] In the vehicle according to the sixth embodiment, the battery pack recovers, for example, regenerative energy of the vehicle's motive power. The vehicle may include a mechanism (regenerator) that converts the kinetic energy of the vehicle into regenerative energy.

[0191] Examples of the vehicle according to the sixth embodiment include a two-wheeled or four-wheeled hybrid electric vehicle, a two-wheeled or four-wheeled electric vehicle, an electric-assisted bicycle, and a railroad car.

[0192] The mounting position of the battery pack in the vehicle according to the sixth embodiment is not particularly limited. For example, when the battery pack is mounted in an automobile, the battery pack can be mounted in the engine compartment, the rear of the vehicle body, or under the seat of the vehicle.

[0193] The vehicle according to the sixth embodiment may be equipped with a plurality of battery packs. In this case, the batteries included in each battery pack may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections. For example, when each battery pack includes a battery pack, the battery packs may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections. Alternatively, when each battery pack includes a single battery, the batteries may be electrically connected in series, electrically connected in parallel, or electrically connected in a combination of series and parallel connections.

[0194] Next, an example of a vehicle according to a sixth embodiment will be described with reference to the drawings.

[0195] FIG. 10 is a partial see-through view that illustrates an example of a vehicle according to the sixth embodiment.

[0196] A vehicle 400 shown in Fig. 10 includes a vehicle body 40 and a battery pack 300 according to the fifth embodiment. In the example shown in Fig. 10, the vehicle 400 is a four-wheeled automobile.

[0197] The vehicle 400 may be equipped with a plurality of battery packs 300. In this case, the batteries (e.g., single cells or assembled batteries) included in the battery pack 300 may be connected in series, in parallel, or in a combination of series and parallel connections.

[0198] 10 illustrates an example in which the battery pack 300 is mounted in an engine room located in the front of the vehicle body 40. As described above, the battery pack 300 may be mounted, for example, in the rear of the vehicle body 40 or under a seat. This battery pack 300 can be used as a power source for the vehicle 400. In addition, this battery pack 300 can recover regenerative energy for the motive power of the vehicle 400.

[0199] Next, an embodiment of a vehicle according to a sixth embodiment will be described with reference to FIG.

[0200] Fig. 11 is a diagram illustrating an example of a control system for an electrical system in a vehicle according to embodiment 6. A vehicle 400 illustrated in Fig. 11 is an electric vehicle.

[0201] The vehicle 400 shown in FIG. 11 comprises a vehicle body 40, a vehicle power supply 41, a vehicle ECU (ECU: Electric Control Unit) 42 which is a higher-level control device of the vehicle power supply 41, an external terminal (terminal for connecting to an external power supply) 43, an inverter 44, and a drive motor 45.

[0202] The vehicle 400 has a vehicle power supply 41 mounted, for example, in an engine compartment, the rear of the vehicle body, or under a seat. Note that, in the vehicle 400 shown in FIG. 11, the mounting location of the vehicle power supply 41 is shown diagrammatically.

[0203] The vehicle power supply 41 includes a plurality of (eg, three) battery packs 300a, 300b, and 300c, a battery management unit (BMU) 411, and a communication bus 412.

[0204] The battery pack 300a includes an assembled battery 200a and an assembled battery monitoring device 301a (for example, VTM: Voltage Temperature Monitoring). The battery pack 300b includes an assembled battery 200b and an assembled battery monitoring device 301b. The battery pack 300c includes an assembled battery 200c and an assembled battery monitoring device 301c. The battery packs 300a to 300c are battery packs similar to the above-mentioned battery pack 300, and the assembled batteries 200a to 200c are assembled batteries similar to the above-mentioned battery pack 200. The assembled batteries 200a to 200c are electrically connected in series. The battery packs 300a, 300b, and 300c can be removed independently and replaced with another battery pack 300.

[0205] Each of the assembled batteries 200a to 200c includes a plurality of unit cells connected in series. At least one of the plurality of unit cells is the secondary battery according to the third embodiment. Each of the assembled batteries 200a to 200c is charged and discharged via a positive terminal 413 and a negative terminal 414.

[0206] The battery management device 411 communicates with the assembled battery monitoring devices 301a to 301c, and collects information on the voltage, temperature, and the like of each of the cells 100 included in the assembled batteries 200a to 200c included in the vehicle power supply 41. In this way, the battery management device 411 collects information on the maintenance of the vehicle power supply 41.

[0207] The battery management unit 411 and the assembled battery monitoring units 301a to 301c are connected via a communication bus 412. In the communication bus 412, one set of communication lines is shared by a plurality of nodes (the battery management unit 411 and one or more assembled battery monitoring units 301a to 301c). The communication bus 412 is a communication bus configured based on, for example, the CAN (Control Area Network) standard.

[0208] The battery pack monitoring devices 301a to 301c measure the voltage and temperature of each of the cells constituting the battery packs 200a to 200c based on commands communicated from the battery management device 411. However, the temperature can be measured at only a few points per battery pack, and it is not necessary to measure the temperatures of all the cells.

[0209] The vehicle power supply 41 may also have an electromagnetic contactor (for example, a switch device 415 shown in FIG. 11) that switches between the presence and absence of an electrical connection between the positive terminal 413 and the negative terminal 414. The switch device 415 includes a pre-charge switch (not shown) that is turned on when the assembled batteries 200a-200c are charged, and a main switch (not shown) that is turned on when the output from the assembled batteries 200a-200c is supplied to a load. Each of the pre-charge switch and the main switch includes a relay circuit (not shown) that is switched on or off by a signal supplied to a coil disposed in the vicinity of the switch element. The electromagnetic contactor such as the switch device 415 is controlled based on a control signal from the battery management device 411 or the vehicle ECU 42 that controls the operation of the entire vehicle 400.

[0210] The inverter 44 converts the input DC voltage into a three-phase alternating current (AC) high voltage for driving the motor. The three-phase output terminals of the inverter 44 are connected to the three-phase input terminals of the drive motor 45. The inverter 44 is controlled based on a control signal from the battery management device 411 or the vehicle ECU 42 for controlling the operation of the entire vehicle. By controlling the inverter 44, the output voltage from the inverter 44 is adjusted.

[0211] The drive motor 45 rotates by electric power supplied from the inverter 44. A driving force generated by the rotation of the drive motor 45 is transmitted to the axles and drive wheels W via, for example, a differential gear unit.

[0212] Although not shown, the vehicle 400 is also equipped with a regenerative braking mechanism (regenerator). The regenerative braking mechanism rotates the drive motor 45 when the vehicle 400 is braked, and converts kinetic energy into regenerative energy as electrical energy. The regenerative energy recovered by the regenerative braking mechanism is input to the inverter 44 and converted into a direct current. The converted direct current is input to the vehicle power source 41.

[0213] One terminal of a connection line L1 is connected to the negative terminal 414 of the vehicle power supply 41. The other terminal of the connection line L1 is connected to a negative input terminal 417 of the inverter 44. A current detection unit (current detection circuit) 416 in the battery management device 411 is provided between the negative terminal 414 and the negative input terminal 417 on the connection line L1.

[0214] One terminal of a connection line L2 is connected to the positive electrode terminal 413 of the vehicle power supply 41. The other terminal of the connection line L2 is connected to a positive electrode input terminal 418 of the inverter 44. A switch device 415 is provided in the connection line L2 between the positive electrode terminal 413 and the positive electrode input terminal 418.

[0215] The external terminal 43 is connected to the battery management unit 411. The external terminal 43 can be connected to, for example, an external power source.

[0216] In response to operational inputs from the driver or the like, the vehicle ECU 42 coordinates with other management devices and control devices including the battery management device 411 to control the vehicle power supply 41, the switch device 415, the inverter 44, etc. Through the coordinated control of the vehicle ECU 42, etc., the output of power from the vehicle power supply 41 and the charging of the vehicle power supply 41 are controlled, and the entire vehicle 400 is managed. Data relating to the maintenance of the vehicle power supply 41, such as the remaining capacity of the vehicle power supply 41, is transferred between the battery management device 411 and the vehicle ECU 42 via a communication line.

[0217] The vehicle according to the sixth embodiment is equipped with the battery pack according to the fifth embodiment. Since the capacity per unit mass of the battery pack is high, the degree of freedom in vehicle design is high. Therefore, it is possible to provide a variety of vehicles without compromising the performance of the vehicle.

[0218] <Example> The above-mentioned embodiment will be described in more detail below based on examples, but the present invention is not limited to the examples listed below.

[0219] <Synthesis> Example 1 As follows: Ti4Nb 10 W4O 45 A titanium-niobium-tungsten composite oxide having the composition represented by the following formula was synthesized by a solid-state reaction method.

[0220] Titanium oxide, niobium oxide, and tungsten oxide were prepared as raw materials. Here, tungsten oxide particles were selected that were finer than the particle diameters of titanium oxide and niobium oxide, and were devised to increase the particle contact points and reaction surface of the tungsten particles. These raw materials were mixed in a predetermined composition ratio and subjected to dry grinding and mixing treatment. The resulting mixture was then placed in an alumina crucible and subjected to firing treatment under conditions of 1100°C and 12 hours in an air atmosphere, and then cooled in the furnace. The fired material was dry-ground, and the ground material was classified to adjust the particle size. In the manner described above, active material powder was obtained.

[0221] (Example 2) to (Example 7) Materials were prepared under the same preparation conditions as in Example 1, except that the composition ratio of titanium oxide, niobium oxide, and tungsten oxide was changed depending on the target composition, to obtain active material powders.

[0222] Example 8 The raw materials were mixed in the same mixing ratio as in Example 1, and tantalum oxide (Ta2O5) was further added to this mixture so that the amount of Ta was 2000 ppm relative to the expected synthesis amount obtained after firing the active material powder. Thereafter, materials were produced under the same production conditions as in Example 1, and active material powder was obtained.

[0223] Example 9 The raw materials were mixed in the same mixing ratio as in Example 1, and potassium oxide (KO) was further added to this mixture so that the amount of K was 1000 ppm relative to the expected synthesis amount obtained after firing the active material powder. Thereafter, a material was produced under the same production conditions as in Example 1, except that the firing temperature was changed to 1050°C, and an active material powder was obtained.

[0224] Example 10 The raw materials were mixed in the same ratio as in Example 1, and iron oxide (Fe2O3) was added to this mixture so that the amount of Fe was 2000 ppm relative to the expected amount of synthesis obtained after firing the active material powder. Thereafter, materials were produced under the same production conditions as in Example 1, and active material powder was obtained.

[0225] Example 11 The raw materials were mixed in the same ratio as in Example 1, and phosphorus oxide (P2O5) was further added to this mixture so that the amount of P was 2000 ppm relative to the expected synthesis amount obtained after firing the active material powder. After that, a material was produced under the same production conditions as in Example 1, except that the firing temperature was changed to 1050°C, and an active material powder was obtained.

[0226] Example 12 The raw materials were mixed in the same mixing ratio as in Example 1, and molybdenum oxide (MoO3) was further added to this mixture so that the amount of Mo was 8000 ppm relative to the expected synthesis amount obtained after firing the active material powder. Thereafter, a material was produced under the same production conditions as in Example 1, except that the firing temperature was changed to 1000°C, and an active material powder was obtained.

[0227] (Example 13) The raw materials were mixed in the same mixing ratio as in Example 1, and zirconium oxide (ZrO2) was further added to this mixture so that the amount of Zr was 2000 ppm relative to the expected synthesis amount obtained after firing the active material powder. Thereafter, materials were produced under the same production conditions as in Example 1, and active material powder was obtained.

[0228] Comparative Example 1 As follows: Ti2Nb 10 W5O 44 and TiNb2WO 10 A titanium-niobium-tungsten composite oxide having the composition represented by the following formula was synthesized by a solid-state reaction method.

[0229] Titanium oxide, niobium oxide, and tungsten oxide were prepared as raw materials. These raw materials were mixed in a specified composition ratio and subjected to dry grinding and mixing. The resulting mixture was then placed in an alumina crucible and fired at 1200°C for 12 hours in an air atmosphere, and then cooled in the furnace. The fired material was dry-ground, and the ground material was classified to adjust the particle size. In the manner described above, oxide powder was obtained.

[0230] <Measurement> The powders obtained in the above examples and comparative examples were observed using a scanning transmission electron microscope. Specifically, as described above in detail, the microstructure was observed using a 10 nm x 10 nm image using a STEM-HAADF image with a spherical aberration correction function. In addition, wide-angle X-ray scattering measurements were performed. The measurements were performed according to the details described above. Crystal structure analysis was performed using the Rietveld method on the obtained spectrum. In addition, ICP emission analysis, BET specific surface area measurement using the N2 gas adsorption method, particle size distribution measurement, and scanning electron microscope observation were performed.

[0231] An example of the results obtained by observing the fine structure using STEM-HAADF images is shown in Figures 12 and 13.

[0232] As a result of structural analysis, the composite oxide obtained in Example 1 was identified as having a crystal structure in which the crystal structures shown in Figs. 1 and 2 are mixed. Specifically, the composite oxide has an orthorhombic crystal structure assigned to the space group Amma (space group number: 63), and has 4 x 4 = 16 rhenium oxide block structures including an octahedral edge-sharing structure, and the ratio of the number of oxygen atoms to the number of metal elements in the unit cell is A. O / A M = 2.50 and a crystal structure that is assigned the space group notation P21 / n (space group number: 14). The rhenium oxide type block structure containing 4 × 4 = 16 blocks, and the ratio of the number of oxygen atoms to the number of metal elements in the unit cell is A O / A M =2.50 was used as the estimated model. When this crystal structure was used as the estimated model, fitting was performed for all peaks except for the heterophase that appears at 5° to 70° with an Rwp value, which is the reliability factor of the Rietveld method, of 9.75%, and it was confirmed that there was no inconsistency in the peak positions and relative intensities, so the crystal structure was identified as above. When the orthorhombic structure in Figure 1 and the monoclinic structure in Figure 2 are considered as units, the mixture ratio was estimated to be 39:61 in terms of molar composition ratio.

[0233] 12 shows an example of a STEM-HAADF image of the microstructure of the composite oxide obtained in Example 1. 4 × 4 rhenium oxide block structures 12 are continuously present, and a monoclinic unit cell 13 and an orthorhombic unit cell 14 can be observed.

[0234] The composite oxide obtained in Comparative Example 1 was identified as having a tetragonal structure as a result of structural analysis. - The crystal structure is assigned to space group 82 (space group number 82). The rhenium oxide block structure, including the tetrahedral corner-sharing structure, is 4×4=16, and the ratio of the number of oxygen atoms to the number of metal elements in the unit cell is A O / A M When this crystal structure is used as the estimated model, the reliability factor of the Rietveld method, R wp The value was fitted to 9.86%, and no inconsistencies were confirmed in the peak positions and relative intensities, so the crystal structure was identified as above.

[0235] 13 shows an example of a STEM-HAADF image of the microstructure of the composite oxide obtained in Comparative Example 1. 4 × 4 rhenium oxide block structures 12 are continuously present, and a unit cell 15 of a tetragonal crystal structure and a tetrahedral corner-sharing structure 16 can be observed.

[0236] <Evaluation of battery performance> The composite oxide powders obtained in the above Examples and Comparative Examples were used as active materials to prepare electrodes as follows.

[0237] First, 100 parts by mass of active material, 6 parts by mass of conductive agent, and 4 parts by mass of binder were dispersed in a solvent to prepare a slurry. The composite material powder obtained by the above-mentioned method was used as the active material. A mixture of acetylene black, carbon nanotubes, and graphite was used as the conductive agent. A mixture of carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) was used as the binder. Pure water was used as the solvent.

[0238] The resulting slurry was then applied to one side of a current collector, and the coating was dried to form an active material-containing layer. An aluminum foil with a thickness of 12 μm was used as the current collector. The current collector and the active material-containing layer were then pressed together to obtain an electrode. The weight of the electrode was 60 g / m 2 It was.

[0239] A non-aqueous electrolyte was prepared as follows. An electrolyte salt was dissolved in an organic solvent to obtain a liquid non-aqueous electrolyte. LiPF6 was used as the electrolyte salt. The molar concentration of LiPF6 in the non-aqueous electrolyte was 1 mol / L. A mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) was used as the organic solvent. The volume ratio of EC to DEC was 1:2.

[0240] A three-electrode beaker cell was fabricated using the electrode obtained by the above-mentioned method as a working electrode, metallic lithium foil as a counter electrode and a reference electrode, and the nonaqueous electrolyte prepared by the above-mentioned method.

[0241] The cycle performance of each of the cells thus fabricated was evaluated. Specifically, the cells were first charged at a temperature of 25° C. with a charging current of 0.2 C until the battery voltage reached 0.4 V. Then, the cells were discharged at a discharging current of 0.2 C until the battery voltage reached 3.0 V. The charge / discharge capacity at this time was measured, and the capacity value per unit mass of the active material was calculated for each of the charge and discharge. The charge / discharge efficiency in the initial charge / discharge was also calculated (initial charge / discharge efficiency=[(initial discharge capacity / initial charge capacity)×100%]).

[0242] 16 is a graph showing the initial charge / discharge curves of the beaker cell. The charge / discharge curves of the cell using the composite oxide obtained in Example 1 are shown by solid lines (charge curve 51 and discharge curve 61). The charge / discharge curves of the cell using the composite oxide obtained in Comparative Example 1 are also shown by dashed lines (charge curve 50 and discharge curve 60).

[0243] Tables 1 and 2 below summarize the details of the composition and crystal structure of the composite oxides synthesized in each Example and Comparative Example, as well as their performance as active materials for batteries. Specifically, the details of the composite oxides include the composition, crystal structure, and molar composition ratio of the composite oxides, the type of added element, and the firing temperature. If no element is added, "-" is written in the column for the added element. The performance as active materials for batteries includes the charge capacity and discharge capacity per mass, and the initial charge / discharge efficiency.

[0244] The composition of the composite oxides shown in Table 1 is a formula obtained by multiplying the chemical formula by a certain coefficient so that the numerical value showing the stoichiometric ratio of the constituent elements becomes an integer. For example, in Examples 1 and 8-13, the composition of the composite oxide is Ti4Nb 10 W4O 45 However, this formula is Ti 0.8 Nb2W 0.8 O 9.0 This formula is equal to the formula obtained by multiplying the above formula by a factor of 5. That is, the composite oxides synthesized in Examples 1 and 8-13 are Li a Ti b Nb2W c O 2b+3c+5+δ and corresponds to a compound where a = 0, b = 0.8, and c = 0.8. The same is true for Examples 2-7, where the numerical values ​​indicating the stoichiometric ratios of the constituent elements are multiplied by a coefficient to make them integers. 10 W5O 44 is Ti 0.4 Nb2WO 8.8 This is equal to the chemical formula obtained by multiplying it by a coefficient of 5.

[0245] [Table 1]

[0246]

Table 2

[0247] As is clear from Table 1 and Table 2, the general formula Li a Ti b Nb2W c O 2b+3c+5+δ represents a composite oxide in which each subscript in the formula satisfies 0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, and 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25, and the crystal structure is at least one of a monoclinic structure and an orthorhombic structure. The active material shows good initial charge-discharge efficiency and has a high charge-discharge capacity per mass. The reason for this is considered to be that tungsten oxide particles are selected so as to suppress the sublimation of tungsten elements and the particle contacts are increased, and firing is performed within a desirable firing temperature range.

[0248] In Comparative Example 1, either the charge-discharge capacity or the initial charge-discharge efficiency was lower than the results of Examples 1-13. This is considered to be because in Comparative Example 1, no improvement was made to the particles and the firing temperature was outside the desirable range, so that the crystal structure did not correspond to either a monoclinic structure or an orthorhombic structure.

[0249] Although the examples showed a part of the composition within the range of the subscripts in the general formula, even a composition other than the composition of the examples can obtain the same effects as the present invention as long as it is within the range. In addition, although the synthesized composite oxide shows an example of the composite oxide synthesized by the solid-phase reaction method, the same effects as those of the composite oxide synthesized by the solid-phase reaction method can be obtained even when using the sol-gel method.

[0250] According to one or more of the embodiments and examples described above, an active material containing a composite oxide is provided. The general formula Li a Ti b Nb2W c O 2b+3c+5+δIt is represented by [formula], and each subscript in the formula satisfies the relationships of 0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, and 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25. The crystal structure is at least one of a monoclinic structure and an orthorhombic structure. The active material according to the embodiment can provide an electrode capable of realizing a high-capacity secondary battery, a high-capacity secondary battery and a battery pack, and a vehicle equipped with the battery pack.

[0251] Although several embodiments of the present invention have been described, these embodiments are presented by way of example and are not intended to limit the scope of the invention. These novel embodiments can be implemented in various other forms, and various omissions, replacements, and changes can be made without departing from the gist of the invention. These embodiments and their modifications are included in the scope and gist of the invention, and are included in the invention described in the claims and the equivalent scope thereof.

[0252] Hereinafter, the invention of the embodiment will be appended.

[0253] <1> General formula Li a Ti b Nb2W c O 2b+3c+5+δ It is represented by [formula] and contains a composite oxide where 0≦a≦b + 3c + 4, 0 < b < 2, 0 < c < 2, and 1.9b + 2.85c + 4.75≦δ≦2.1b + 3.15c + 5.25. The crystal structure of the composite oxide is an active material that is at least one of a monoclinic structure and an orthorhombic structure.

[0254] <2> The composite oxide has a vertex-sharing structure including a rhenium oxide-type block structure composed of 16 octahedrons sharing vertices, and the active material according to <1>.

[0255] <3> The vertex-sharing structure is the active material according to <1> or <2>, where the blocks of the block structure share the edges of the octahedrons.

[0256] <4> Further comprising one or more elements selected from the group consisting of V, Ta, Fe, Bi, Sb, As, P, Cr, Mo, B, Na, K, Mg, Al, Ca, Y, Zr, and Si; <1> from <3> 13. The active material according to claim 12 .

[0257] <5> <1> from <4> 13. An electrode comprising the active material according to claim 12.

[0258] <6> A positive electrode and A negative electrode; An electrolyte; At least one of the positive electrode and the negative electrode comprises <5> A secondary battery comprising the electrode according to claim 1.

[0259] <7> <6> A battery pack comprising the secondary battery according to claim 1.

[0260] <8> An external terminal for supplying electricity; A protection circuit; Further comprising: <7> The battery pack according to claim 1 .

[0261] <9> A battery comprising a plurality of the secondary batteries, The secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel. <7> or <8> The battery pack according to claim 1 .

[0262] <10> <7> from <9> A vehicle comprising the battery pack according to any one of claims 1 to 5.

[0263] <11> A mechanism for converting the kinetic energy of the vehicle into regenerative energy. <10> A vehicle as described in. [Explanation of symbols]

[0264] 1...electrode group, 2...exterior member, 3...negative electrode, 3a...negative electrode current collector, 3b...negative electrode active material containing layer, 4...separator, 5...positive electrode, 5a...positive electrode current collector, 5b...positive electrode active material containing layer, 6...negative electrode terminal, 7...positive Pole terminal, 10...monoclinic structure, 10a...octahedral, 11...orthorhombic structure, 11a...octahedron, 12...block structure, 13...unit cell, 14...unit cell, 15...unit cell, 16...vertex sharing structure, 1 8...metal element, 19...oxygen element, 21...bus bar, 22...positive electrode lead, 23...negative electrode lead, 24...adhesive tape, 31...container, 32...lid, 33...protective sheet, 34...printed wiring board, 35...wiring, 40...vehicle body, 41...vehicle power source, 42...electrical control device, 43...external terminal, 44...inverter, 45...driving motor, 100...secondary battery, 200...battery pack, 200a ... battery pack, 200b... battery pack, 200c... battery pack, 300... battery pack, 300a... battery pack, 300b... battery pack, 300c... battery pack, 301a... battery pack monitoring device, 301b... battery pack monitoring device, 301c... battery pack monitoring device, 342... positive connector, 343... negative connector, 345... thermistor, 346... protection circuit, 342a... wiring, 343a... wiring, 35 0...external terminal for current supply, 352...positive terminal, 353...negative terminal, 348a...positive wiring, 348b...negative wiring, 400...vehicle, 411...battery management device, 412...communication bus, 413...positive terminal, 414...negative terminal, 415...switch device, 416...current detection unit, 417...negative input terminal, 418...positive input terminal, L1...connection line, L2...connection line, W...drive wheel.

Claims

1. General formula Li a Ti b Nb 2 W c O 2b+3c+5+δ wherein 0≦a≦b+3c+4, 0<b<2, 0<c<2, and 1.9b+2.85c+4.75≦δ≦2.1b+3.15c+5.25 are satisfied, The composite oxide has at least one of a monoclinic structure and an orthorhombic structure as a crystal structure of the active material.

2. The active material according to claim 1 , wherein the composite oxide has a corner-sharing structure including a rhenium oxide type block structure in which 16 octahedra are configured by corner-sharing.

3. The active material according to claim 2 , wherein the corner-sharing structure is such that blocks of the block structure share edges of the octahedron.

4. 10. The active material of claim 1, further comprising one or more elements selected from the group consisting of V, Ta, Fe, Bi, Sb, As, P, Cr, Mo, B, Na, K, Mg, Al, Ca, Y, Zr, and Si.

5. An electrode comprising the active material of claim 1.

6. A positive electrode and A negative electrode; An electrolyte; and at least one of the positive electrode and the negative electrode is the electrode according to claim 5.

7. A battery pack comprising the secondary battery according to claim 6.

8. An external terminal for supplying electricity; A protection circuit; The battery pack of claim 7 further comprising:

9. A battery comprising a plurality of the secondary batteries, The battery pack according to claim 7 , wherein the secondary batteries are electrically connected in series, in parallel, or in a combination of series and parallel.

10. A vehicle comprising the battery pack according to claim 7.

11. The vehicle of claim 10 including a mechanism for converting kinetic energy of the vehicle into regenerative energy.

Citation Information

Patent Citations

  • Active material for batteries, nonaqueous electrolyte battery and battery pack

    JP2016177972A

  • Active material, electrode, secondary battery, battery pack, and vehicle

    JP2020047374A

  • Active material, electrode, secondary battery, battery pack, and vehicle

    JP2022048576A

  • Secondary battery, battery pack, and vehicle

    JP2023026188A

  • Niobium titanium-based oxide, electrode, secondary battery, battery pack, vehicle, and stationary power source

    JP2024037659A